2008
DOI: 10.1104/pp.108.121038
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Arabidopsis Gene Expression Uncovers a Complex Array of Changes Impacting Pathogen Response and Cell Cycle during Geminivirus Infection  

Abstract: Geminiviruses are small DNA viruses that use plant replication machinery to amplify their genomes. Microarray analysis of the Arabidopsis (Arabidopsis thaliana) transcriptome in response to cabbage leaf curl virus (CaLCuV) infection uncovered 5,365 genes (false discovery rate ,0.005) differentially expressed in infected rosette leaves at 12 d postinoculation. Data mining revealed that CaLCuV triggers a pathogen response via the salicylic acid pathway and induces expression of genes involved in programmed cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
384
3
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(427 citation statements)
references
References 107 publications
17
384
3
3
Order By: Relevance
“…These genes have been implicated in DNA repair (Doucet-Chabeaud et al, 2001;De Block et al, 2005) and have been shown to be associated with chromosomes through their N-terminal zinc fingers (Babiychuk et al, 2001). AtPARP1 and AtPARP2 are up-regulated during geminivirus infection, most likely in response to accumulation of nicked viral DNA forms (Ascencio-Ibanez et al, 2008), and also accumulate under conditions of DNA stress (Culligan et al, 2006). The finding that two putative transcriptional coactivators can bind to the zinc fingers of AtPARP1 suggests that, like mammalian PARP-1, this protein may also be involved in regulation of gene expression in addition to its role in DNA repair (Storozhenko et al, 2001).…”
mentioning
confidence: 92%
“…These genes have been implicated in DNA repair (Doucet-Chabeaud et al, 2001;De Block et al, 2005) and have been shown to be associated with chromosomes through their N-terminal zinc fingers (Babiychuk et al, 2001). AtPARP1 and AtPARP2 are up-regulated during geminivirus infection, most likely in response to accumulation of nicked viral DNA forms (Ascencio-Ibanez et al, 2008), and also accumulate under conditions of DNA stress (Culligan et al, 2006). The finding that two putative transcriptional coactivators can bind to the zinc fingers of AtPARP1 suggests that, like mammalian PARP-1, this protein may also be involved in regulation of gene expression in addition to its role in DNA repair (Storozhenko et al, 2001).…”
mentioning
confidence: 92%
“…Among them, the jasmonate response, dependent on the SCF COI1 complex, plays a crucial role in pathogen defenses. Not much information about the role of jasmonates on viral infection is currently available, but recent works revealed jasmonate signaling as an emerging topic in plant-virus interaction research (Vigliocco et al, 2002;Liu et al, 2004;Agudelo-Romero et al, 2008;Ascencio-Ibá ñ ez et al, 2008;Yang et al, 2008;Kovac et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Table S10) (58,59). Orthogroup 1685 encodes a cysteine-rich receptor-like protein kinase, and the ortholog in Arabidopsis (AT1G70520) is up-regulated during pathogen infection and rapid cell death (51).…”
Section: Intron Positions Are Highly Conserved (Si Appendixmentioning
confidence: 99%